Deconstructing Colonial Law Through Critical Race Theory in Indonesian Regulations - Suyuti Dahlan Rifa’i; Mahrus Alwi Hasan Siregar; Indah Pratiwi Utami; Ach Mujahid; Adinda Zeranica Putri Fakhis (Jurnal Pelita Raya, 2025)
This study aims to map patterns of discrimination arising from colonial legacies, whether in the form of legal norms, institutions, or law enforcement practices, and to offer an alternative perspective that can elevate the experiences of marginalised groups as a basis for national legal reform. This study employs a critical qualitative method grounded in document and critical discourse analysis, particularly by adopting Critical Race Theory (CRT) as its primary theoretical and methodological framework. The results of the deconstruction of colonial law through Critical Race Theory (CRT) clearly show that the Indonesian national legal system still harbours residues of colonial discrimination and bias, so that administrative revisions alone are not sufficient to eradicate entrenched injustice. Therefore, a paradigm shift and transformative legal reform are needed, one that dares to place the experiences of marginalised groups at the centre of renewal, to build a legal structure that is truly inclusive, fair, and responsive to the needs of all citizens. This is the time for the Indonesian nation to commit to legal decolonisation that is not merely symbolic but real and liberating to achieve substantive justice that upholds humanity.